Shorebird Abundance and Species Richness in Penang Island - Razak, Nur Asnida A; Rahman, Azimah Abd (European Publisher, 2019)
Mangroves area is one type of landscape in Malaysia that sustains various species of shorebirds. Throughout the years, several species of shorebirds are experiencing tremendous declination in population size. Therefore, the species are classified as endangered and near-threatened under the IUCN Red List of Threatened Species. Development of coastal wetlands for industrial needs and human disturbances are two major factors affecting the number of the migrating species. This study focused on the abundance and species richness of shorebirds at two main sites i.e. Teluk Air Tawar and Kuala Muda. The birds were observed and counted using a point count method from November 2017 to January 2018. Abiotic factors included temperature, humidity, and light intensity was also studied. A total of 3293 birds, belonging to four families were recorded i.e. Scolopacidae, Ardeidae, Charadriidae, and Laridae. Among these, the family Scolopacidae was the most abundant which accounted for 85% of the total birds at Teluk Air Tawar and 61% at Kota Kuala Muda. The family Laridae was least abundant family at both sites with the percentage of 1% at Teluk Air and 5% at Kota Kuala Muda. Research findings showed that Teluk Air Tawar was an ideal habitat for several shorebirds due to the bigger mangrove estuary than Kota Kuala Muda. It functions as a breeding site for aquatic organisms as well as providing shelter for various bird species including shorebirds. Therefore, conservation efforts should be implemented to continuously preserve and protect the mangrove areas to benefit both human and wildlife populations.